The Azerbaijani Attempts to Falsify the History of the 89th Armenian Triple Order Bearer Tamanyan Division - Minasyan, Edik (History and Culture, 2022)
In the article “It is Easy to Rewrite a Wikipedia Article, but You Can’t Hide the Cowardice,” written by Oleg Kuznetsov, there is obviously incorrect information containing a certain intent on the glorious combat path of the 89th Armenian Rifle Division. The author of the article deliberately disseminates false information about the activities of the military units of the USSR during the Great Patriotic War. The article contains a disrespectful, insulting attitude towards the Soviet military, whose representatives fought in the ranks of the 89th Infantry Division. Using the example of the failures of the 89th division, the author deliberately forms a negative perception of the Armenian ethnos by the Russian-speaking audience. O. Kuznetsov, citing fictitious facts discrediting Armenia, pursues obvious pro-Azerbaijani goals. We have raised all the necessary questions in order to provide clarifications and present the truth.